2002
DOI: 10.1016/s0370-2693(01)01525-8
|View full text |Cite
|
Sign up to set email alerts
|

String balls at the LHC and beyond

Abstract: In string theory, black holes have a minimum mass below which they transition into highly excited long and jagged strings -"string balls". These are the stringy progenitors of black holes; because they are lighter, in theories of TeV-gravity, they may be more accessible to the LHC or the VLHC. They share some of the characteristics of black holes, such as large production cross sections. Furthermore, they evaporate thermally at the Hagedorn temperature and give rise to high-multiplicity events containing hard … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
194
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(197 citation statements)
references
References 24 publications
3
194
0
Order By: Relevance
“…This has led to the advocacy of the choice Q ≃ r −1 s [11], which has the advantage of a sensible limit at very high energies. However, as has been pointed out by Dimopoulos and Emparan [48], string progenitors can give experimental signals akin to BH for the collision energies and values of M min BH under present consideration. In cosmic ray experiments, these signals are indistinguishable from those of BH decay (more on this below).…”
Section: Implications For Tev-scale Gravitymentioning
confidence: 61%
“…This has led to the advocacy of the choice Q ≃ r −1 s [11], which has the advantage of a sensible limit at very high energies. However, as has been pointed out by Dimopoulos and Emparan [48], string progenitors can give experimental signals akin to BH for the collision energies and values of M min BH under present consideration. In cosmic ray experiments, these signals are indistinguishable from those of BH decay (more on this below).…”
Section: Implications For Tev-scale Gravitymentioning
confidence: 61%
“…This is the "remnant phase", in which the theoretical modelling uncertainties are large. The conventional treatment by the event generators used in LHC simulations is to decay the black hole remnant to a small number of SM particles [21].…”
Section: Jhep08(2014)103mentioning
confidence: 99%
“…This is the "remnant phase", in which the theoretical modelling uncertainties are large. The conventional treatment by the event generators used in LHC simulations is to decay the black hole remnant to a small number of SM particles [21].Strong gravitational states include, in the context of weakly coupled string theory, highly excited string states (string balls) [22]. 1 In these models, the string scale M S [23] and string coupling g S define M D = g −2/(n+2) S M S and determine the string ball properties.…”
mentioning
confidence: 99%
“…Below the GR threshold, quantum gravity effects are expected to manifest. It has been shown that highly excited string states, known as string balls [6], produced below the GR threshold, could have a cross section comparable to that of a black hole. Furthermore, black holes produced at the LHC could evolve into these string states.…”
Section: String Ballsmentioning
confidence: 99%
“…In this paper a selected overview of search strategies for different types of signatures is given. It is also shown how the results can be interpreted in models of SUSY, extra dimensions [3][4][5] and string balls [6].…”
Section: Introductionmentioning
confidence: 96%